FAKTOR – FAKTOR YANG MENGHAMBAT PENGELOLAAN STADION UTAMA RIAU (SUR) - Syafrianda "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Management of Riau Main Stadium (SUR) has many obstacles and constraints. The obstacles can be seen from the ownership status of SUR that unclear from year 2013 – 2015, in 2012 after the implementation of PON in Riau Province. The ownership of SUR due to uncertainty of regarding the status of the debts helps by the Provincial Government to the contractor building in the stadium. Consequently have an impact on not managed of SUR, resulting SUR be groomed and well maintained. It can be seen from the surrounding area of the stadium which is already covered by bushes, and damaged several other supporting infrastructure such as building toilets, ticket purchases, and so on, by November 2016.This study uses the concept by theory Yusuf (2015), which states that in relation to the rules - the rules that limit, at least - there is at least three factors that need to be considered in the optimization of the regional asset value of the asset, the asset functions, as well as asset management systems and procedures. This study uses qualitative research with an assessment of descriptive data. Data collection techniques were collected by the researcher through observation, interviews, and documentation.This results indicate a conclusion that the factors that hinder SUR management deals with three problems with the environment of space. Namely the limited authority of Dispora manage, not the allocation of budget funds to meet development needs and repayment of debt, and also the scope of time to complete the stage-by-stage problems that stadium, because it is the next necessary seriousness for the government in managing the assets that exist in Riau including SUR, one of them with a good understanding in managing assets - public assets in an integrated and strategic by considering environmental aspects, sustainability, and the demands of society.Key Words : Regional Autonomy, Asset Management, Riau Main Stadium